Volatile Constituents from the Fruits of Lindera glauca (Sieb. et Zucc.) with Different Maturities. Issue 4 (18th May 2016) - Zhu, Baoqing; Hou, Xinyu; Niu, Jun; Li, Peixue; Fang, Chenglian; Qiu, Lin; Ha, Denglong; Zhang, Zhixiang; Sun, Jiaqi; Li, Yibo; Lin, Shanzhi
Abstract: The volatiles of Lindera glauca (Sieb. et Zucc.) fruits with different maturities, grown in Jigongshan mountain, Henan China, were isolated by hydro-distillation method and analyzed by GC-qMS. Eighty seven constituents were identified in the essential oil from the middle July samples, comprising 73.94 % of the volatiles, and the major components were sesquiterpene hydrocarbons (40.02%) and monoterpene hydrocarbons (30.61%), of which β-ocimene (12.99%) is the major one, followed by α-pinene (4.07%) and β-caryophyllene (3.73%). In the oil from the middle August samples, the major components of the identified 72 components, comprising 88.64% of the essential oil, were monoterpene hydrocarbons (57.75%) and sesquiterpene hydrocarbons (28.83%), and also β-ocimene (37.40%) is the major constituent, followed by caryophyllene (3.71%), myrene (3.54%) and α-pinene (3.35%). While in the essential oil isolated from fully ripe fruits collected in middle September, 74 constituents comprising 87.27% which included 20 monoterpenoids (44.71%) and 43 sesquiterpenoids (38.32%) were identified, and β-ocimene was also the major constituent (30.30%). It was also noticed that the volatile content rose along with the maturity of the fruits. The essential oil yields in the above three samples were 0.6%, 1.2% and 1.4%, respectively.